The earthly and sacred in the semantics of the tuvinians’ traditional costume; Журнал Сибирского федерального университета. Серия: Гуманитарные науки; Т. 12, № 12 - Kukhta M. S. Maria Sergeevna (2019, 2019)
Title screen